2015
DOI: 10.1002/dmrr.2677
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection is associated with type 2 diabetes among a middle‐ and old‐age Chinese population

Abstract: These findings suggested that H. pylori infection was associated with the risk of type 2 diabetes in a middle-age and old-age Chinese population. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 34 publications
0
37
0
1
Order By: Relevance
“…Therefore, it is plausible that chronic H. pylori infection might predispose individuals to hyperglycemia. Consistent with this notion, several studies on non‐diabetic individuals showed positive associations between H. pylori infection and glycemia or metabolic syndrome, with only a few exceptions. However, in patients with type 2 diabetes, the association between H. pylori infection and hyperglycemia remains inconclusive.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, it is plausible that chronic H. pylori infection might predispose individuals to hyperglycemia. Consistent with this notion, several studies on non‐diabetic individuals showed positive associations between H. pylori infection and glycemia or metabolic syndrome, with only a few exceptions. However, in patients with type 2 diabetes, the association between H. pylori infection and hyperglycemia remains inconclusive.…”
Section: Introductionmentioning
confidence: 84%
“…It is thus not surprising that when using serum or urine IgG assay as the diagnostic method, no relationship between H. pylori infection and glycemia exists in studies of non‐diabetic individuals. In contrast, a positive relationship between H. pylori infection and glycemia or metabolic syndrome is noted in mainly or exclusively non‐diabetic individuals, when applying diagnostic tests that verify active H. pylori infection. Thus, it is evident that active or inactive infection affects the relationship between H. pylori infection and glycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, H. pylori infection was also associated with a higher risk of type 2 diabetes (OR=1.08; CI: 1.02–1.14; P =.008) after adjustment for other confounders. The same authors underlined that subjects with H. pylori infection had a lower level of high‐density lipoprotein cholesterol ( P <.0001) and higher blood pressure levels ( P <.001), total cholesterol, HbA1c, and fasting blood glucose ( P <.0001) compared to H. pylori ‐negative ones . On the contrary, Tamura et al.…”
Section: Diabetes Mellitus and Metabolic Syndromementioning
confidence: 97%
“…Researchers have also found that infection with H. pylori can result in cardiovascular, hematological, hepatobiliary, and metabolic diseases (5)(6)(7)(8)(9). Currently, many epidemiological surveys have been performed to identify risk factors for H. pylori infection; age, obesity, and type 2 diabetes mellitus have been identified as risk factors (10)(11)(12)(13). In terms of diagnosis, stool antigen testing, gastric biopsies, CLO-test, and urea breath test are used.…”
Section: Introductionmentioning
confidence: 99%